Postcolonial Perspectives on the Inclusion of Immigrant Students in Galiza, Spain - Teasley, Cathryn (Education Policy Analysis Archives, 2008)
This study offers a critical exploration of educational policy in Galiza (or Galicia), Spain, in light of the growing cultural diversity of its population and its own socio-cultural history. By situating schools' "welcoming" (acogida), or reception and inclusion, of immigrant students within a broad, transversal terrain of postcolonial and relational (McCarthy, 1993 and 2005) analysis–one that traverses disciplinary perspectives and national and historical contexts–the main intent is to reflect on specific aspects of the official inclusion policy in order to help transform schooling into a more just and integrative cross-cultural institution. A series of ethnographic observations currently underway in educational communities of the four provinces of Galiza will provide some initial impressions of this policy as seen from the necessary perspectives of practice in schools. Some key questions include: What relevance does the postcolonial perspective have for the educational integration of immigrant students in Galiza? Does the mere development of a postcolonial awareness among teachers and students, as well as a relational understanding of today's world, constitute a potentially transformational, even emancipatory, pedagogical and curricular intervention? It is argued that it does, to the extent that it reveals the assimilationist orientation of integration, in the currently predominant approaches to inclusion or welcoming.